Near- and middle-ultraviolet reconfigurable Raman source using a record-low UV/visible transmission loss inhibited-coupling hollow-core fiber. (March 2022) - Chafer, M.; Osório, J.H.; Dhaybi, A.; Ravetta, F.; Amrani, F.; Delahaye, F.; Debord, B.; Cailteau-Fischbach, C.; Ancellet, G.; Gérôme, F.; Benabid, F.
Highlights: Two types of Raman sources emitting in the near and middle ultraviolet. New record low-loss inhibited-coupling hollow-core fiber (5 dB/km at 480 nm). Raman comb in a hydrogen-filled HCPCF with lines from 270 nm to the near-infrared. Dual-wavelength Raman source tuned to the ozone absorption band in the ultraviolet. Sources exhibit a very small footprint and are solarization-free. Abstract: We report on two types of Raman laser sources emitting in the near and middle ultraviolet spectral ranges by the use of a solarization-resilient gas-filled inhibited-coupling (IC) hollow-core photonic-crystal fiber (HCPCF) with record low transmission loss (minimum of 5 dB/km at 480 nm). The first source type emits a Raman comb generated in a hydrogen-filled HCPCF pumped by a 355 nm wavelength microchip nanosecond pulsed laser. The generated comb lines span from 270 nm to the near-infrared region with no less than 20 lines in the 270–400 nm wavelength range. The second type stands for the first dual-wavelength Raman source tuned to the ozone absorption band in the ultraviolet. Such dual-wavelength source emits at either 266 nm and 289 nm, or 266 nm and 299 nm. The relative power of the pair components is set to optimize the sensitivity of ozone detection in differential absorption lidar (DIAL). The source's physical package represents more than 10-fold size-reduction relative to current DIAL lasers, thus opening new opportunities in on-field ozone monitoring and mapping. Both Raman sources exhibit a very small footprint and are solarization-free.